Fatigue crack propagation in thin walled structures - Kanbak, Yiğit (Graduate School, 2024)
In engineering, damage tolerance can be defined as durability of a structure in the presence of a crack. Damage tolerance applications are used in variety of engineering disciplines to control the extension of a crack such as aerospace engineering, mechanical engineering and civil engineering. If the structure can be maintained before when the failure occurs, this structure said to be damage tolerant. The study examined how tolerant the C shape beam was against damages. In this study, a C shape beam was analyzed with using Ansys Workbench software. It is intended to determine how many cycles can the beam endure under 0-1 kN variable load. Since several difficulties were encountered when performed tests using the beam, a plate was preferred to use to do tests and analyzes. Firstly, in the intend of getting elasticity modulus and young's modulus of the material tensile test was done. Following this, crack propagation tests were done in Composite and Structure laboratory, ITU Aerospace Engineering Faculty, with the plate. An analysis was also done to get a model for the plate. When compared, it was seen that there was a 29% difference among tests and analyzes results. Model which was used for the plate was used for the beam. In the analysis, linear elastic fracture mechanics assumptions were used which were: material is isotropic and linearly elastic. Linear tetrahedral elements were used for the model. For whole body 10 mm elements, near the crack tip 0.15 mm elements were used. Element sizes were at its optimum level in terms of solution time and precision of solution. Pre-meshed crack option of the software was used to define the crack. The dimensions of C shape beam was specified with respect to literature. The beam was applied 0-1000 N varying force. The applying force was ramped. Finally, it was found that the beam could endure this load along 107 cycles.
İnce cidarlı yapılarda yorulmayla çatlak ilerlemesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: crack propagation; çatlka yayılımı; structural failures; yapısal kırılmalar